Patients With Voice Prosthesis Rehabilitation During the COVID‐19 Pandemic: Analyzing the Effectiveness of Remote Triage and Management. (4th August 2020) - Longobardi, Ylenia; Galli, Jacopo; D'Alatri, Lucia; Savoia, Vezio; Mari, Giorgia; Rigante, Mario; Passali, Giulio Cesare; Bussu, Francesco; Parrilla, Claudio
Abstract : Objective: To describe a remote approach used with patients with voice prosthesis after laryngectomy during the COVID‐19 pandemic and the resulting clinical outcomes in terms of voice prosthesis complications management, oncological monitoring, and psychophysical well‐being. Study Design: Prospective cohort study. Setting: Otolaryngology Clinic of the University Polyclinic A. Gemelli, IRCCS Foundation. Subjects and Methods: All patients with voice prosthesis who underwent laryngectomy followed by our institute were offered enrollment. Patients who agreed to participate were interviewed to inquire about the nature of the need and to plan a video call with the appropriate clinician. Before and 1 week after the clinician's call, patients were tested with the Hospital Anxiety and Depression Scale. Degrees of satisfaction were investigated with a visual analog scale. A comparison between those who accepted and refused telematic support was carried out to identify factors that influence patient interest in teleservice. Results: Video call service allowed us to reach 37 (50.68%) of 73 patients. In 23 (62.16%) of 37 cases, the video call was sufficient to manage the problem. In the remaining 14 cases (37.83%), an outpatient visit was necessary. Participants who refused telematic support had a significantly shorter time interval from the last ear, nose, and throat visit than patients who accepted (57.95 vs 96.14 days, P =. 03). Video‐called patients showed significantly decreased levels of anxiety and depression (mean Hospital Anxiety and Depression Scale total score pre– vs post–video call: 13.97 vs. 10.23, P <. 0001) and reported high levels of satisfaction about the service. Conclusion: Remote approach may be a viable support in the management of patients with voice prosthesis rehabilitation.